Definition of acquired toxoplasmosis infection: When is it congenital or acquired? (2011)
We read with great interest the article by Álvarez et al. recently published in the Spanish Ophthalmological Society on the clinical characteristics of ocular toxoplasmosis in an immigrant population in Barcelona, Spain.1 It is noteworthy that the authors defined as congenital forms the presentations with a large macular atrophic scar and pigmented edges. Traditionally, the presence of lesions at the macular level has been considered a sign of congenital toxoplasmosis. However, as described by Holland in a recent review on the influence of age in ocular toxoplasmosis,2 more recent studies show that the presence of macular lesions does not differentiate reliably between congenital infections and those acquired after birth. A study carried out by ourselves3 describes the clinical characteristics of ocular toxoplasmosis in a Colombian cohort where the acquisition of the infection was determined in only 30% of patients (20% congenital, 10% acquired), with a large percentage (70%) remaining undetermined precisely because it is not possible to demonstrate whether the infection of a patient was acquired after birth if there is no evidence of seroconversion or serological demonstration of an acute infection (IgM+, IgG?) and subsequent positivization of the IgG antibodies, discarding natural IgM antibodies. Moreover, it is not possible to determine in an adult that the infection was congenital if there is no certainty about the infection being diagnosed at the prenatal level by means of the techniques described in literature, either immunological such as avid IgG, IgA, or through molecular biology with the PCR of gene B1 in amniotic liquid.